Identifying Natural Therapeutics against Diabetes via Inhibition of Dipeptidyl Peptidase 4: Molecular Docking and MD Simulation Study - Kausar, Mohd Adnan; Shahid, SMA; Anwar, Sadaf; Kuddus, Mohammed; Khan, Mohammad Kalim Ahmad; Alotaibi, Abdullah Dakheel; Arif, Jamal Mohammad (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: As per the International Diabetes Federation statistics 2019, about 463 million people aged between 20-79 years have diabetes, in which mortality of 1.6 million individuals have been recorded each year, especially in developing and economically impoverished countries. Despite the people’s equal access to basic facilities of appropriate healthcare systems and lifesaving drugs, it is desirable to accelerate the identification and development of natural drug candidates, prophylactically and therapeutically promising against the disease, thereby strengthening universal health coverage of Sustainable Development Goals. Materials and Methods: The research aims to identify natural inhibitor molecules targeting dipeptidyl peptidase 4 using docking and molecular dynamics simulation studies followed by metabolism and biological activity prediction. Data set of sixteen natural molecules considered to perform molecular interaction studies using AutoDock Tools. Results: Sitagliptin exhibited stronger binding (ΔG: -8.63 kcal/mol, Ki: 10.12 μM) with dipeptidyl peptidase 4 among their all-known inhibitors. Among natural compounds, apigenin, bromelain, cholecalciferol, isoimperatorin, luteolin, neohesperidin, oleanoic acid depicted excellent binding affinities with the target in comparison to sitagliptin as reflected by their ΔG (> -9 kcal/mol) values. The top two ligands-neohesperidin (ΔG: -9.86 kcal/mol) and bromelain (-9.79 kcal/mol), and the known drug sitagliptin was selected for molecular dynamics (MD) simulation to assess stabilities of their docked complexes. Conclusion: Post analysis of MD study, CYP450 metabolism prediction and biological activity spectrum identification favour the antidiabetic potential of bromelain.
Keywords: Diabetes; Dipeptidyl peptidase 4; Natural therapeutics; Molecular docking; MD simulation; Sustainable development goals